Determinants of prolonged exclusive breastfeeding among children aged 6–23 months in 21 sub-saharan African countries: evidence from nationally representative data - Enyew Getaneh Mekonen (Italian Journal of Pediatrics)
Abstract Background Under-five mortality and malnutrition are more common in many low- and middle-income countries, highlighting the grave consequences of improper nutrition for children. Infants that continue to be exclusively breastfed after six months are considered to be engaging in prolonged exclusive breastfeeding. Children with prolonged exclusive breastfeeding are more susceptible to anemia, atopic dermatitis, and food allergies. There is no evidence on the pooled prevalence and determinants of prolonged exclusive breastfeeding in sub-Saharan Africa. Therefore, this study is intended to determine the prevalence and associated factors of prolonged exclusive breastfeeding among children aged 6 to 23 months in sub-Saharan African countries. Methods Data from the recent demographic and health surveys of 21 countries in sub-Saharan Africa conducted between 2015 and 2022 were used. A total weighted sample of 63,172 mother-child pairs was included in the current study. Multilevel mixed-effects logistic regression was used to determine the factors associated with the outcome variable. Intra-class correlation coefficient, likelihood ratio test, median odds ratio, and deviance (-2LLR) values were used for model comparison and fitness. Finally, variables with a p-value < 0.05 and an adjusted odds ratio with a 95% confidence interval were declared statistically significant. Results The pooled prevalence of prolonged exclusive breastfeeding among children aged 6–23 months in sub-Saharan Africa was 17.32% (95% CI: 17.03%, 17.62%). Factors like child age [AOR = 4.39; 95% CI (4.17, 4.62)], wealth index [AOR = 1.15; 95% CI (1.07, 1.23)], maternal educational level [AOR = 1.56; 95% CI (1.36, 1.78)], marital status of the mother [AOR = 1.11; 95% CI (1.04, 1.19)], media exposure [AOR = 1.11; 95% CI (1.06, 1.17)], place of delivery [AOR = 0.82; 95% CI (0.78, 0.87)], postnatal checkup [AOR = 1.43; 95% CI (1.36, 1.51)], drinking water source [AOR = 1.06; 95% CI (1.01, 1.11)], sanitation facility [AOR = 1.15; 95% CI (1.10, 1.21)], antenatal care attendance [AOR = 1.27; 95% CI (1.16, 1.39)], community literacy [AOR = 1.08; 95% CI (1.02, 1.15)], and community media exposure [AOR = 1.06; 95% CI (1.01, 1.13)] were significantly associated with prolonged exclusive breastfeeding. Conclusions Nearly one out of five children aged 6–23 months in sub-Saharan Africa had prolonged exclusive breastfeeding. Both individual- and community-level factors were significantly associated with prolonged exclusive breastfeeding. Policymakers could find it very important to support maternal education, poverty reduction, media exposure, maternal healthcare services, and complementary feeding hygiene practices in order to encourage the timely initiation of complementary feeding.